Upaya Menjaga Kelestarian Bahasa Sasak Halus Melalui Program Binaan Desa - Azhari, Supian; Alfan Hadi; Samsul Hakim (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
This research departs from a problem that occurs in Pejanggik Village, Central Praya District related to the shift of the subtle Sasak language which should be preserved and used as a communication tool in interacting so that this subtle Sasak language is not lost to the times.  The purpose of this study are (1) to preserve the subtle Sasak language that exists in the area of the island of Lombok sasa West Nusa Tenggara NTB. (2) to find out the obstacles and the impact of the occurrence of language shift ayng used daily in communication carried out by the people of Pejanggik Village, Central Praya District.  (3) to know the solution to overcome the obstacles and the impact faced in the impact of the occurrence of language shift ayng used daily in communication carried out by the people of Pejanggik Village, Central Praya Subdistrict. The method used in this research is qualitative descriptive research method with the type of field research, to analyze data in the form of sentences or words. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data is analyzed by data reduction, data presentation, and data verification or data summarization. The results of the study are (1). With the existence of this fine Sasak language assistance program, it can reduce the shift of Sasak language in the village of Pejanggik, Central Praya kecamtan. (2) As for the impact of this fine Sasak language coaching procurement program, the youth and the community look enthusiastic in participating in these activities. And this program can solve the problems that occur in pejanggik village. (3). with the procurement of the subtle Sasak language coaching program organized by the pejanggik village government has a positive impact on the community as well as children and youth in general.